2017
DOI: 10.1002/2017gl072926
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes and anomalous self‐diffusion of oxygen in liquid iron at high pressure

Abstract: We report structural properties and diffusivity of liquid Fe0.96O0.04 over a density range of 5.421–11.620 g cm−3, corresponding to pressures of 0–330 GPa and 2200–5500 K, using first‐principles molecular dynamics. We predict a change in compression mechanism near 8 g cm−3. At lower density, Fe and O coordinations increase from ~10 to ~13 and ~3 to ~6, respectively, the average Fe–O distance increases from ~1.81 Å to ~1.88 Å, and the Fe–Fe distance remains essentially constant. Calculated oxygen diffusivities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
10
14
0
Order By: Relevance
“…Another evidence comes from diffusion properties in liquid iron alloy. Our calculated diffusion rates of Fe, Si, and O agree well with previous calculations and experiments on liquid Fe, Fe–O, Fe–Si, or Fe–Si–O under core conditions (Alfè et al, ; Posner, Rubie, et al, ; Posner, Steinle‐Neumann, et al, ; Pozzo et al, ; Vočadlo et al, ). In particular, the well‐equilibrated liquid Fe 0.79 Si 0.08 O 0.13 ternary at 4000 K and 136 GPa from Pozzo et al () not only provides almost identical diffusion coefficients of Fe, Si, and O as in our calculations but also is at odds with the proposed SiO 2 exsolution isotherms (Hirose et al, ) by having higher concentrations of Si and O than what the precipitation model allows for (Figure S3).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Another evidence comes from diffusion properties in liquid iron alloy. Our calculated diffusion rates of Fe, Si, and O agree well with previous calculations and experiments on liquid Fe, Fe–O, Fe–Si, or Fe–Si–O under core conditions (Alfè et al, ; Posner, Rubie, et al, ; Posner, Steinle‐Neumann, et al, ; Pozzo et al, ; Vočadlo et al, ). In particular, the well‐equilibrated liquid Fe 0.79 Si 0.08 O 0.13 ternary at 4000 K and 136 GPa from Pozzo et al () not only provides almost identical diffusion coefficients of Fe, Si, and O as in our calculations but also is at odds with the proposed SiO 2 exsolution isotherms (Hirose et al, ) by having higher concentrations of Si and O than what the precipitation model allows for (Figure S3).…”
Section: Resultssupporting
confidence: 89%
“…At 136 GPa and 3800 K, we find D Fe = 0.4·10 −8 m 2 /s, D Si = 0.3·10 −8 m 2 /s, and D O = 1.0·10 − 8 m 2 /s: Fe and Si have very similar diffusion coefficients, whereas D O is about 3 times faster. These data agree with those obtained from liquid iron ( D Fe = 0.4–0.5·10 −8 m 2 /s; Posner, Rubie, et al, ; Vočadlo et al, ), Fe–O ( D Fe = 0.8·10 −8 m 2 /s and D O = 10 −8 m 2 /s; Alfè et al, ; Posner, Steinle‐Neumann, et al, ), Fe–Si–O ( D Fe = D Si = 0.4–0.5·10 −8 m 2 /s and D O = ~1.3·10 −8 m 2 /s; Pozzo et al, ) under core conditions. This excellent agreement further confirms that the Fe 86 Si 11 O 11 mixture remains a single well‐mixed liquid under all conditions (Figure S3).…”
Section: Resultssupporting
confidence: 86%
“…Indeed, recent experiments have presumed V φ of the solid FeS 2 is equivalent to V P of the liquid counterpart and thus estimated the sulfur content in Earth’s outer core 43 . Furthermore, in the I 4/ mmm -type Fe 2 O, the coordination number of oxygen is eight and each iron is surrounded by four oxygen and nine iron, which is similar to the recent report of structural properties of the liquid oxygen-bearing iron alloys by first-principles molecular dynamics 44 . Thus, it is reasonable that the target system can be used to roughly derive the amount of oxygen in the lower outer core.…”
Section: Discussionsupporting
confidence: 88%
“…For Si and Cr, we have previously described “iron‐like” behavior in which the alloying element exhibits essentially identical structural and transport properties to those of iron (Posner, Rubie, Frost, Vlček, et al, ). On the other hand, oxygen shows “non‐iron‐like” behavior with diffusion being 2–3 times faster than for iron and exhibiting an atomic radius that is smaller by ~20% (Alfè et al, ; Ichikawa & Tsuchiya, ; Posner, Steinle‐Neumann, et al, ). In this study, we extend our previous computational work on Fe alloys with O, Si, and Cr in terms of structural and transport properties of liquid iron alloys at high pressure (Posner, Rubie, Frost, Vlček, et al, ; Posner, Steinle‐Neumann, et al, ) to H, C, N, Mg, S, and Ni.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a set of previous experimental (Posner, Rubie, Frost, & Steinle‐Neumann, ) and computational studies (Posner, Steinle‐Neumann, et al, ) have shown a negligible activation volume (Δ V ) for oxygen diffusion in liquid iron below ~5 GPa, which is the pressure of the δ γ ‐liquid triple point (e.g., Strong et al, ). At higher P , Δ V becomes positive, and this change is associated with an increase in NOFec from ~3 to ~6 (Posner, Steinle‐Neumann, et al, ), following the observation of a bcc‐like to fcc‐like structural transformation in liquid Fe (Sanloup et al, ). The change in NOFec also provides a plausible explanation of the change in metal‐silicate/oxide partitioning of oxygen over this P range (e.g., Asahara et al, ; Frost et al, ).…”
Section: Introductionmentioning
confidence: 99%